SAT0236 Safety and disease activity changes in an extension of a phase IIB study of atacicept in patients with SLE (address II). (15th June 2017) - Wallace, DJ; Isenberg, D; Wax, S; Kao, A; Chang, P; Fraser, PA; Merrill, JT
Abstract : Background: We previously reported results of the 24-week phase IIb ADDRESS II study of atacicept, which demonstrated clinical response in patients with autoantibody-positive SLE, particularly those with high disease activity (HDA; SLEDAI 2K ≥10 at screening). Objectives: This extension study of ADDRESS II evaluated safety and disease activity in patients with SLE given continued atacicept treatment to week 48 (NCT01972568 ). Methods: Atacicept was given as weekly subcutaneous injection to completers of ADDRESS II on average for an additional ≥24 weeks (i.e. ≥48 weeks total from Day 1 of ADDRESS II). Patients already receiving atacicept continued on the same dose (75 mg or 150 mg); those receiving placebo (PBO) switched to atacicept 150 mg (PBO/150 mg). Results: Of 262 patients completing ADDRESS II, 253 (95%) entered the extension (PBO/150 mg n=83; 75 mg n=82; 150 mg n=88). Demographics were balanced between groups, and most patients were female (91.3%) and white (70%). All three treatment groups had similar rates of treatment-emergent adverse events (TEAEs), TEAEs leading to treatment discontinuation, serious TEAEs, and serious/severe infection (Table 1 ). Two deaths occurred in the 150 mg arm, considered unrelated to treatment (reported events of stroke and abdominal pain with hematemesis). In the ITT population (n=253), SLE responder index (SRI)-4 rates were maintained between weeks 24 and 48 in the original atacicept groups (75 mg 56.9 vs 55.9%; 150 mg 53.8 vs 56.7%) and moderately increased in the PBO/150 mg group (44.0 vs 48.0%). This improvement was greater for SRI-6 in the HDA subpopulation (PBO/150 mg 28.8% at week 24 vs 42.3% at week 48; 75 mg 41.8 vs 54.5%; 150 mg 54.9 vs 60.8%; Figure 1 ). The proportion of HDA patients achieving SLEDAI scores ≤2 was also maintained in the atacicept groups (75 mg 20.0 vs 21.8%; 150 mg 37.3 vs 39.2%) and increased in the PBO/150 mg group (13.5 vs 19.2%). In the ITT and HDA populations, most flares occurred before week 24, with reduced risk of severe (BILAG A) and moderate/severe (BILAG A/2B) flares afterwards. Some increase in complement C3 and C4, and decrease in anti-dsDNA antibodies occurred after week 24. Serum IgG decreased moderately, without severe hypogammaglobulinemia (IgG <3 g/L) in any patients. Conclusions: There were no new safety signals with atacicept between week 24 and 48, and clinical responses achieved during the first 24 weeks were maintained. Acknowledgements: The study was sponsored by EMD Serono Research & Development Institute Inc., USA (a business of Merck KGaA, Germany). Medical writing support was provided by Bioscript Science, UK, and funded by Merck KGaA, Germany. Disclosure of Interest: D. Wallace Consultant for: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, D. Isenberg Consultant for: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, S. Wax Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, A. Kao Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, P. Chang Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, P. Fraser Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, J. Merrill Consultant for: Anthera Pharmaceuticals, Lilly, EMD Serono, GlaxoSmithKline and Biogen